Monitoring intrapartum fetal heart rates by mothers in labour in two public hospitals: an initiative to improve maternal and neonatal healthcare in Liberia - K. Borzie; N. Jasper; D. P. Southall; R. MacDonald; A. A. Kola; O. Dolo; A. Magnus; S. D. Watson; M. Casement; B. Dahn; W. Jallah (BMC, 2020)
Abstract Background In low-resource settings with few health workers, Fetal Heart Rate (FHR) monitoring in labour can be inconsistent and unreliable. An initiative to improve fetal monitoring was implemented in two public hospitals in rural Liberia; the country with the second lowest number of midwives and nurses in the world (1.007 per 10,000 of the population). The initiative assessed the feasibility of educating women in labour to monitor their own FHR and alert a midwife of changes detected. Methods Four hundred seventy-four women admitted in labour without obstetric complications were approached. Four hundred sixty-one consented to participate (97%) and 13 declined. Those consenting were trained to monitor their FHR using a sonicaid for approximately 1 minute immediately following the end of every uterine contraction and to inform a midwife of changes. If changes were confirmed, standard clinical interventions for fetal distress (lateral tilt, intravenous fluids and oxygen) were undertaken and, when appropriate, accelerated delivery by vacuum or Caesarean section. Participants provided views on their experiences; subsequently categorized into themes. Neonatal outcomes regarding survival, need for resuscitation, presence of birth asphyxia, and treatment were recorded. Results Four hundred sixty-one out of 474 women gave consent, of whom 431 of 461 (93%) completed the monitoring themselves. Three hundred eighty-seven of 400 women who gave comments, reported positive and 13 negative experiences. FHR changes were reported in 28 participants and confirmed in 26. Twenty-four of these 26 FHR changes were first identified by mothers. Fetal death was identified on admission during training in one mother. Thirteen neonates required resuscitation, with 12 admitted to the neonatal unit. One developed temporary seizures suggesting birth asphyxia. All 26 neonates were discharged home apparently well. In 2 mothers, previously unrecognized obstetric complications (cord prolapse and Bandl's ring with obstructed labour) accompanied FHR changes. Resuscitation was needed in 8 neonates without identified FHR changes including one of birth weight 1.3 Kg who could not be resuscitated. There were no intrapartum stillbirths in participants. Conclusions Women in labour were able to monitor and detect changes in their FHR. Most found the experience beneficial. The absence of intrapartum stillbirths after admission and the low rate of poor neonatal outcomes are promising and warrant further investigation.